2019
DOI: 10.1111/pin.12808
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of whole slide imaging for primary diagnosis of lymphoma

Abstract: Whole slide imaging (WSI) is being increasingly used worldwide. Although previous studies have asserted the validity of WSI diagnosis, they have primarily targeted only small specimens and excluded cases requiring immunohistochemistry or special staining, such as lymphoma. The purpose of this study was to evaluate the accuracy of WSI diagnosis of lymphoma, for which 240 biopsies and resections of lymphoma cases were selected from the study set of lymphomas. All slides including H&E, immunohistochemical and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, most of previously published studies mainly targeted small specimens and excluded cases requiring immunohistochemistry, such as lymphoma cases. So far there is only one published report investigating the concordance rate between digital pathology and conventional microscopic histopathology and the researchers found that WSI was a reliable technology for lymphoma diagnosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of previously published studies mainly targeted small specimens and excluded cases requiring immunohistochemistry, such as lymphoma cases. So far there is only one published report investigating the concordance rate between digital pathology and conventional microscopic histopathology and the researchers found that WSI was a reliable technology for lymphoma diagnosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the acquisition of high-magnification images is generally recommended. Although evidence is lacking about diagnostic agreement at different scanning magnifications, results to date have shown less than 1% of major discordance between WSI-based and microscopic diagnoses using a basic 20 × scan [54]. Moreover, the recorded 6.25% of minor discordance was mostly due to differences in grading follicular lymphoma and was similar to the inter-and intra-observer diagnostic discordance in microscopic diagnosis [54].…”
Section: Scope Of Applicationmentioning
confidence: 80%
“…Although evidence is lacking about diagnostic agreement at different scanning magnifications, results to date have shown less than 1% of major discordance between WSI-based and microscopic diagnoses using a basic 20× scan [ 54 ]. Moreover, the recorded 6.25% of minor discordance was mostly due to differences in grading follicular lymphoma and was similar to the inter- and intra-observer diagnostic discordance in microscopic diagnosis [ 54 ]. Because pathologic diagnosis of lymphoreticular neoplasms is almost always made in combination with the results of additional tests, such as immunohistochemical staining, diagnostic differences in the findings of H&E slide images alone do not seem to significantly affect diagnostic accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We highlight three recent articles that have broken the mold by expanding the application of WSI to include hematopathology and reflect on our recent relevant work. [ 5 6 7 ] The first article assessed the usefulness of WSI for the diagnosis of lymphoma[ 5 ] and the other publications employed deep learning with a convolutional neural network (CNN) algorithm to build diagnostic lymphoma models. [ 6 7 ]…”
mentioning
confidence: 99%